Heritage Trails and Cycling Tourism in City Branding: Exploring the Nexus of Experiences and Expectations - Prastyadewi, Made Ika; Nursanty, Eko; Pramandari, Putu Yusi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This paper delves into the intricate relationship between heritage trails and cycling tourism, specifically focusing on the case study of the heritage-rich city of Surakarta. The convergence of heritage trails and cycling tourism forms a dynamic nexus that influences both the experiences of tourists and their expectations. The notion of the